PELAKSANAAN TUGAS BAGIAN LINEN DEPARTEMENT HOUSKEEPING HOTEL TJOKRO KOTA PEKANBARU - Muhammad Zaki; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Increasing amount traveler influential to existence of hotels. In Pekanbaru, an increase amount visitor Also happened at Tjokro Hotel Pekanbaru. this _ influential Also to enhancement amount visiting guests _ And stay. So from it, Housekeeping Department on linen section of Tjokro Hotel Pekanbaru. Study This use method descriptive qualitative for analyze problem based on data collection in the form of observation, interview deep, and documentation. implementation task covers carry out sorting and counting linen, distributing linen, carrying out inventory of linen, repair of damaged linen, receiving clothes uniform employee, save all linens. For whole from results observation and interview, data is withdrawn conclusion say that implementation task Housekeeping Department at the linen section yet fully walk with existing standards. Keywords: Hotel, Housekeeping Department, Linen Section, Implementation Task